METHODS OF THE MORALE ASSESSING OF PERSONNEL OF THE ARMED FORCES OF UKRAINE DURING THE SPECIAL PERIOD - Мась, Н. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
In the article the author proposes a methodology for evaluating morale of personnel during of assigned tasks during the Special Period. Keywords: methods, moral and psychological state, personnel, index, level, the special period.